Common Mesophilic Anaerobes, Including Clostridium botulinum and Clostridium tetani, in 21 Soil Specimens - Smith, Louis Ds. (1975)
A relatively rich medium was markedly superior to a dilute medium for the isolation of anaerobic bacteria from soil. The obligate anaerobes isolated from 21 soil samples were all clostridia and the counts ranged from 2.7 × 10(2) to 3.3 × 10(6) per g. The organisms most frequently isolated were Clostridium subterminale, C. sordellii, C. sporogenes, C. indolis, C. bifermentans, C. mangenoti, and C. perfringens. Seventeen other species were also recognized but almost one-third of the isolates could not be identified with any known species of Clostridum. C. botulinum type A was demonstrated in six soil samples, and type B in one. These soils were neutral to alkaline in reaction (average pH 7.9) and low in organic matter content (1.4%). The association of C. botulinum types A and B with neutral to alkaline soils was statistically significant (P = 0.001) as was their association with soils low in organic matter (P = 0.005). C. botulinum types E and F were found in one soil sample, pH 4.5, with organic matter 13.7%. C. tetani was isolated from two soil samples, both of intermediate pH value and higher than average organic matter content.